Zemlia ottsov . The Land of the Fathers - Aimanov, Shaken (Kazakhfilm, 1966)
Duration: 01:25:00 "The Land of the Fathers" is one of the outstanding Kazakh films of the Soviet epoch. Since it was shot during the "Thaw," the director was able to portray truly national characters and their resistance to the Soviet ideology. The leading characters - an old man and his grandchild - travel by train through Kazakhstan to Russia in order to search for the remains of the kid's father (the old man's son) who perished during Wolrd War II and to carry the remains back to Kazakhstan for burial. The mission fails because the soldier was buried in a common grave. During the trip the old man and his grandson Bayan come across different people and various mundane situations, which help the boy see the special place of national values in the big world around him. The film starts off with a close-up of a tombstone with an epitaph in Arabic. This frame, as well as other references to Muslim prayers and customs in the movie, were indeed a bold decision on the part of the director, considering the period during which the movie was shot and the possible repercussions. These episodes, however, alongside with other traditional attributes of the Kazakh world - steppe, river, sound of the dombra, etc. encapsulate the ethical codes that are central to the concept of the film. The action that takes places on the road builds on yet another strong code - the nomadic lifestyle of the Kazakhs. The encounters are not mere elements of the plot, but help reaffirm the deeper meaning of the traditional Kazakh wolrldview and values against those of other, "Western", "modern" cultures. Despite official acknowledgment and a number of domestic and international prizes garnered by it, the film is undeservedly forgotten, although it is truly one of the outstanding works of Soviet Asian cinematography.